Heterologous fibrin sealant potentiates axonal regeneration after peripheral nerve injury with reduction in the number of suture points - Leite, Ana Paula Silveira [UNESP] (2019)
The use of suture associated with heterologous fibrin sealant has been highlighted for reconstruction after peripheral nerve injury, having the advantage of being safe for clinical use. In this study we compared the use of this sealant associated with reduced number of stitches with conventional suture after ischiatic nerve injury. 36 Wistar rats were divided into 4 groups: Control (C), Denervated (D), ischiatic nerve neurotmesis (6 mm gap); Suture (S), epineural anastomosis after 7 days from neurotmesis, Suture + Fibrin Sealant (SFS), anastomosis with only one suture point associated with Fibrin Sealant. Catwalk, electromyography, ischiatic and tibial nerve, soleus muscle morphological and morphometric analyses were performed. The amplitude and latency values of the Suture and Suture + Fibrin Sealant groups were similar and indicative of nerve regeneration.The ischiatic nerve morphometric analysis in the Suture + Fibrin Sealant showed superior values related to axons and nerve fibers area and diameter when compared to Suture group. In the Suture and Suture + Fibrin Sealant groups, there was an increase in muscle weight and in fast fibers frequency, it was a decrease in the percentage of collagen compared to group Denervated and in the neuromuscular junctions, the synaptic boutons were reestablished.The results suggest a protective effect at the lesion site caused by the fibrin sealant use. The stitches reduction minimizes the trauma caused by the needle and it accelerates the surgical practice. So the heterologous fibrin sealant use in nerve reconstruction should be considered.